Social determinants of student mental health before and after the Beirut port explosion: two cross-sectional studies - Julia Scheuring; Tania Bosqui (Conflict and Health)
Abstract Background Students in Lebanon are facing the devastating impact of multiple national crises, including an unprecedented economic collapse and the Beirut port explosion that killed hundreds, injured thousands, and displaced hundreds of thousands of people. The aim of this study was to identify key social determinants of common mental health symptoms before and after the Beirut port explosion for students at the American University of Beirut, a university based around 4 km from the port. Methods Two cross-sectional studies were conducted using a representative sample of undergraduate and graduate students at the American University of Beirut. The study was conducted just before (Study 1) and repeated after the Beirut port explosion (Study 2). Results A total of 217 students participated (n = 143 in Study 1 and n = 74 in Study 2). In Study 1 before the explosion, poorer family functioning and social support were correlated with higher levels of depressive symptoms, but not with anxiety or trauma symptoms. Financial stress was correlated with depressive and trauma symptoms. In the partially adjusted regression model (adjusting for demographics), only financial stress was significantly associated with depressive symptoms. In the fully adjusted model (adjusting for adversity), financial stress was associated with depressive and anxiety symptoms. In Study 2 after the explosion, poorer family functioning and poorer social support were correlated with higher levels of depressive symptoms, while only poorer social support was correlated with higher levels of anxiety symptoms—trauma symptoms were not correlated with either. Financial stress was correlated with all symptoms. In the partially adjusted regression model, only financial stress was significantly associated with all symptom clusters. In the fully adjusted model, no variables were significant. Conclusion Findings indicate a detrimental impact of financial stress on the mental health of students in Lebanon, beyond the otherwise protective effects of family and social support, in the context of an unprecedented economic crisis and extremely high levels of distress after the explosion. Findings indicate that mental health interventions for college students in Lebanon should include addressing financial stress, and that further research is needed to identify protective factors during acute emergencies.